The Piano Works of Claude Debussy - Schmitz, Robert (New York Courier Dover, 1966)
Part biography, part criticism, and part analysis, this fascinating study of one of music's greatest geniuses is above all an authoritative commentary on the entire corpus of Debussy's work for solo piano. Written with special insights for the performer. Includes 21 illustrations.
Keywords: Debussy, Claude -- 1862-1918; 19th Century (1801-1900); 20th Century (1901-2000); Keyboard music; Piano; Musical analysis; France